2021
DOI: 10.1016/j.cej.2020.127081
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation, binary modelling and artificial neural network prediction of surfactant adsorption for enhanced oil recovery application

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 102 publications
2
34
0
Order By: Relevance
“…e static experiment indicated that the nanionic surfactant has more adsorption density with respect to the anionic surfactant. e ANN model revealed good agreement with the experimental result, and also, the results showed that adsorption density for both surfactants decreases as temperature increases [42]. Das et al (2020) measured the adsorption density of a nanionic surfactant with two different types of hydrophobic units and hydrophilic polyethoxylate units ranging from 15 to 40 mers on Indiana limestone.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…e static experiment indicated that the nanionic surfactant has more adsorption density with respect to the anionic surfactant. e ANN model revealed good agreement with the experimental result, and also, the results showed that adsorption density for both surfactants decreases as temperature increases [42]. Das et al (2020) measured the adsorption density of a nanionic surfactant with two different types of hydrophobic units and hydrophilic polyethoxylate units ranging from 15 to 40 mers on Indiana limestone.…”
Section: Introductionsupporting
confidence: 59%
“…Ahmed F. Belhaj et al (2021) investigated the adsorption behavior of two chemical surfactant nanionic alkyl polyglucoside (APG) and anionic alkyl ether carboxylate (AEC) on the carbonate surfactant using static adsorption experiments and artificial neural network (ANN) prediction. e static experiment indicated that the nanionic surfactant has more adsorption density with respect to the anionic surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Since no cross reactions were observed for determination of PYR, 2-NT and EBZA (Figure S8C), these three VOCs were then simultaneously detected using this SERS nose.The SERS intensity ratio (I 1236 /I 1530 ,I 1375 /I 1530 and I 1690 /I 1530 )showed agood linearity with logarithmic VOCconcentration over the range from 10 ppb to 1000 ppm, due to Te mkin adsorption of VOCs on SERS substrates [33] (Figure S8B). Thel imits of detection (LODs) were estimated to be 7.6 AE 0.7, 5.3 AE 0.6, and 4.1 AE 0.5 ppb for PYR, 2-NT and EBZA, respectively, which were 10 times lower than those obtained by GC-MS [12] and fluorescence spectroscopy, [13] 100 times lower than those obtained by electrochemical methods [14] (Table S8).…”
Section: Vocs Detection Of Human Eb Based On the Sers Nosementioning
confidence: 99%
“…The claim that artificial neural networks are useful tools because they can minimize the time of experimental treatment and operating costs can be contrasted in different studies reported in the bibliography. An example of this, is the study carried out by Belhaj et al [37] in which they use artificial neural networks to predict absorption values for alkyl ether carboxylate (AEC) and alkyl polyglucoside (APG). Thus, this book chapter summary the research carried out in our research group to predict density, speed of sound, kinematic viscosity and surface tension of amphiphilic aqueous solutions [13].…”
Section: Representation Of a Typical Neural Network With 3 Neurons In The Input Layer 5 Neurons In One Hidden Layer And One Neuron In Thementioning
confidence: 99%